Comparison of Happiness and Life Satisfaction in Athletes and Non-Athletes Postmenopausal Women - Najmeh Hamid; Sepideh Abdoli; Manije Shehni (Fasa University of Medical Sciences, 2020)
Background & Objective: The aim of present study was to compare happiness and life satisfaction in athlete and non-athlete postmenopausal women. Materials & Methods: This comparative study was the causal type of corelational studies. The sample of this study included all 49-59 years old athlete and non-athlete postmenopausal women in the city of Dezful, Iran. The 100 athletes and non-athletes postmenopausal were selected by cluster sampling method. They were homogenized based on age, educational status, not suffering from acute physical and mental disorder and other criteria considered in this research. The instruments were Oxford happiness questionnaire and life satisfaction inventory. The data were analyzed using multi-variate analysis of variance method. Results: The results revealed that there was a significant difference between athlete and non-athletes in terms of happiness and its subscales including self-esteem, subjective well-being, positive mood and life satisfaction (P<0.001). The results showed that athlete postmenopausal women were significantly better than non- athlete postmenopausal women in happiness and life satisfaction. Conclusion: It seems that regular physical activity has desirable effect on post-menopausal women. These results indicated that regular physical activity exercise decreased mental side effect of postmenopausal athlete compared to postmenopausal women.